Green Initiatives: Challenges in Sustainment - Subramaniam, D. (Prabandhan: Indian Journal of Management, 2012)
This article examines the Green initiatives taken by several environmental agencies and challenges in sustaining these initiatives. It also explores what sort of incentives and penalties the state can think of in creating the awareness and in making the movement sustainable. The paper uses a number of real life learning experiences that have happened in the global context.